2016
DOI: 10.1002/2016ja023458
|View full text |Cite
|
Sign up to set email alerts
|

Observations of turbulence in a Kelvin‐Helmholtz event on 8 September 2015 by the Magnetospheric Multiscale mission

Abstract: Spatial and high‐time‐resolution properties of the velocities, magnetic field, and 3‐D electric field within plasma turbulence are examined observationally using data from the Magnetospheric Multiscale mission. Observations from a Kelvin‐Helmholtz instability (KHI) on the Earth's magnetopause are examined, which both provides a series of repeatable intervals to analyze, giving better statistics, and provides a first look at the properties of turbulence in the KHI. For the first time direct observations of both… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
95
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 97 publications
(109 citation statements)
references
References 90 publications
11
95
0
Order By: Relevance
“…The E spectral index dramatically steepens at frequencies above ~3 f lh (~20 Hz). These observations are consistent with previously reported turbulence spectra in the magnetosphere with the exception that B has a shallower spectral index between f ci and f lh (Ergun et al, ; Stawarz et al, ).…”
Section: Observationssupporting
confidence: 93%
See 1 more Smart Citation
“…The E spectral index dramatically steepens at frequencies above ~3 f lh (~20 Hz). These observations are consistent with previously reported turbulence spectra in the magnetosphere with the exception that B has a shallower spectral index between f ci and f lh (Ergun et al, ; Stawarz et al, ).…”
Section: Observationssupporting
confidence: 93%
“…Plasma turbulence is active in many astrophysical settings (e.g., the interstellar medium Falceta‐Gonçalves et al, ). It is central to the solar corona (e.g., Cranmer et al, ), the solar wind (e.g., Matthaeus et al, ), and active regions of the Earth's magnetosphere (Borovsky et al, ; Borovsky & Funsten, ; Chasapis et al, ; Stawarz et al, ; Stawarz, Ergun, & Goodrich, ; Vörös et al, ; Weygand et al, ; Zimbardo et al, ). In particular, plasma sheet turbulence is well established (ibid).…”
Section: Introductionmentioning
confidence: 99%
“…The latter decouples from the magnetic field and typically shows a steeper and much more variable power law (e.g., Šafránková et al 2016). On the contrary, the electric field spectrum flattens (Bale et al 2005;Sahraoui et al 2009;Salem et al 2012), dominating over the magnetic field's, with a typical spectral index of about −0.8 (e.g., Stawarz et al 2016;Matteini et al 2017), as predicted from the generalized Ohm's law (Franci et al 2015a). Moreover, an increase in the magnetic compressibility Kiyani et al 2013) and a reduced variance anisotropy (Podesta & TenBarge 2012) are also observed.…”
Section: Introductionmentioning
confidence: 94%
“…The Kelvin‐Helmholtz (KH) instability driven by a large sheared flow (Chandrasekhar, ) is often considered as one of the major mechanisms of the “viscous‐like” interaction (Axford, ) between the solar wind and the Earth's magnetosphere during northward interplanetary magnetic field (IMF) conditions (Johnson et al, ). Nonlinear KH waves are ubiquitously observed by different spacecrafts (Chen & Kivelson, ; Eriksson et al, ; Fairfield et al, ; Hasegawa et al, , ; Li et al, ; Nakamura et al, ; Nykyri et al, ; Stawarz et al, ; Vernisse et al, ) at low latitudes under both northward and southward IMF conditions (Hwang et al, ; Kavosi & Raeder, ; Walsh et al, ; Yan et al, ), as well as at high latitudes for dawnward and duskward IMF conditions (Hwang et al, ; Ma, Otto, Delamere, et al, ), which are consistent with global magnetohydrodynamics (MHD) simulations (Guo et al, ; Hwang et al, ; Li et al, ; Merkin et al, ). Therefore, it is of importance to identify and quantify how efficiently the nonlinear KH instability transports magnetic flux, mass, flux tube entropy, and momentum.…”
Section: Introductionmentioning
confidence: 99%